2017
DOI: 10.3171/2016.7.peds16204
|View full text |Cite
|
Sign up to set email alerts
|

QuickBrain MRI for the detection of acute pediatric traumatic brain injury

Abstract: OBJECTIVE The current gold-standard imaging modality for pediatric traumatic brain injury (TBI) is CT, but it confers risks associated with ionizing radiation. QuickBrain MRI (qbMRI) is a rapid brain MRI protocol that has been studied in the setting of hydrocephalus, but its ability to detect traumatic injuries is unknown. METHODS The authors performed a retrospective cohort study of pediatric patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
(25 reference statements)
0
21
0
1
Order By: Relevance
“…Similarly, symptoms of brain damage including TBI may not be apparent until the child begins to develop and mature behaviorally and cognitively. A current effective method for diagnosing neonatal TBI acutely is computer tomography (CT) scanning, however, doctors are often hesitant to submit the newborn to CT due to the risks associated with ionizing radiation [49]. As a result of the limited diagnosing ability, stem cell therapy may not feasible as an acute treatment.…”
Section: Caveats and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, symptoms of brain damage including TBI may not be apparent until the child begins to develop and mature behaviorally and cognitively. A current effective method for diagnosing neonatal TBI acutely is computer tomography (CT) scanning, however, doctors are often hesitant to submit the newborn to CT due to the risks associated with ionizing radiation [49]. As a result of the limited diagnosing ability, stem cell therapy may not feasible as an acute treatment.…”
Section: Caveats and Future Directionsmentioning
confidence: 99%
“…To make acute stem cell therapy effective, a method of diagnoses must be developed that does not harm the neonate. A possible area of development is in highly sensitive imaging technologies, such as quickbrain MRI, which removes the radiation concern [4951]. …”
Section: Caveats and Future Directionsmentioning
confidence: 99%
“…A few small studies have suggested that rapid MRI can be used to detect clinically significant intracranial injury that would require neurosurgical intervention, but the sensitivity for trace extra-axial hemorrhages of a few millimeters in width has been questioned. In one study of 54 children by Sheridan et al [6], rapid brain MRI demonstrated 85% sensitivity for all intracranial traumatic injuries, with small extraaxial hemorrhages missed in 4 children. At our institution, we previously evaluated 102 hemorrhages in children and demonstrated an overall sensitivity of 86% for subdural or epidural hemorrhages with rapid MRI [7].…”
mentioning
confidence: 99%
“…MR imaging is not established for routine use in acute pediatric brain trauma yet, though several studies have validated the ability of MR imaging to detect relevant pathology and have shown the feasibility of rapid MR imaging protocols. [6][7][8] The use of radiographs in minor pediatric head trauma is controversial. In patients with linear skull fractures on radiographs and who are asymptomatic, there may still be small intracranial hemorrhages, but these would not require neurosurgical intervention.…”
mentioning
confidence: 99%